(untitled) (Revista de História da UEG (REVHIST), 2012)
Este artigo dedica-se a analisar a concepção historiográfica de Pierre Daunou, procurando mostrar características e ambigüidades deste político francês que também se fez historiador. O artigo examina mais especificamente o texto de época que levou o título de “Discurso de Abertura do Curso de História pronunciado no Collège de France em 13 de abril de 1819”. PIERRE DAUNOU: A SPEECH ABOUT HISTORY Abstract: This article aims to examine the historiographical conception of Pierre Daunou, trying to show features and ambiguities of this French politician who also produced historiographic works. The article examines, with more specificity,the text entitled “Open Discourse of the History Curse pronounced on the Collége de France in April 13 of 1819”.